Upaya Peningkatan Hasil Belajar Siswa pada Materi Bagian Tubuh Tumbuhan Melalui Model Problem Based Learning - Putri Indah Meilansari; Nurul Kusuma Dewi; Tri Susi Artina Wati (Universitas Palangka Raya, 2024)
This research aims to measure the learning outcomes of class IV students at SDN Kertobanyon regarding plant body parts and their functions using a problem based learning model. This research involved 13 class IV students at SDN Kertobanyon using the Classroom Action Research (PTK) method. Data was collected through the pre-cycle, cycle I and cycle II stages. The research results show a significant increase in student learning outcomes. At the pre-cycle stage, the percentage of students whose learning outcomes reached the KKM was 38.5%. In the first cycle stage, the percentage of students whose learning outcomes reached the KKM was 46.1%. In cycle II stage, the percentage of students whose learning outcomes reached the KKM was 76.9%. The PBL model has proven to be effective not only in increasing understanding of science and science concepts, but also in developing students' social skills and learning motivation. Therefore, PBL is recommended as an effective learning model for science and science learning in elementary schools.